LAND POSSESSION RIGHTS AND ITS AFFAIR - I Made Suwitra (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Land right control under customary law that was communal religious in nature tend to control insecular individual manner despite being controlled by the customary law. Land right registrationis motivated more by intention to transfer the land right. These two conditions may result inconflict and affect the conflict settlement. The land right registration in the context of AgrarianLaw can unintentionally result in conflict due to ignorance of the process in the customary law,or the land right is controlled using the ownership pattern as of Agrarian Law context. Thesettlement of such conflict can be done through non-litigation or litigation manner, but litigationis preferred since it is considered to give legal certainty.Key word: Land Tenure, Conflict Implication